2005
DOI: 10.1080/15472450590912529
|View full text |Cite
|
Sign up to set email alerts
|

An Agent-Based Approach to Assess Drivers' Interaction with Pre-Trip Information Systems

Abstract: Article:Rossetti, R. and Lui, R. (2005) An agent-based approach to assess drivers' interaction with pre-trip information systems. Journal of Intelligent Transportation Systems., 9 (1). pp. This article reports on the practical use of a multi-agent microsimulation framework to address the issue of assessing drivers' responses to pretrip information systems. The population of drivers is represented as a community of autonomous agents, and travel demand results from the decision-making deliberation performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Most studies with this approach have focused on investigating the impact of information on route choice behavior. As could be expected, such studies (Nakayama et al, 1999;Horowitz 1984;Iida et al, 1992;Cantarella and Cascetta, 1995;Jha et al, 1998;Oh et al, 2003;Rossetti and Liu, 2005) found that the drivers' route choice could be affected by their earlier experiences. Recently, Srinivasan (2003) considered the disutility from changing paths to describe route choice behavior, and Nakayama et al (1999Nakayama et al ( , 2000Nakayama et al ( , 2001 developed a rule-based model to study drivers' route choice behavior.…”
Section: Traveler Behavior and Day-to-day Evolution Approachmentioning
confidence: 54%
“…Most studies with this approach have focused on investigating the impact of information on route choice behavior. As could be expected, such studies (Nakayama et al, 1999;Horowitz 1984;Iida et al, 1992;Cantarella and Cascetta, 1995;Jha et al, 1998;Oh et al, 2003;Rossetti and Liu, 2005) found that the drivers' route choice could be affected by their earlier experiences. Recently, Srinivasan (2003) considered the disutility from changing paths to describe route choice behavior, and Nakayama et al (1999Nakayama et al ( , 2000Nakayama et al ( , 2001 developed a rule-based model to study drivers' route choice behavior.…”
Section: Traveler Behavior and Day-to-day Evolution Approachmentioning
confidence: 54%
“…Fujiwara et al indicated that the informed level of travel service given by pre-trip information significantly affects the departure time choice [18]. Rossetti and Lui revealed that the overall performance of the pre-trip information was very likely affected by exogenous information, as ascribed to demand formation and network topology [19]. Shiftan et al confirmed that pre-trip travel time information has an impact on route-choice behavior and underscored that when experience seeking increases, individuals tend to prefer a route characterized by lower average but greater variance of travel time [20].…”
mentioning
confidence: 99%
“…As it stands, it is also possible to use the tool to perform altitude queries for single points (as opposed to annotating an entire network file). The tool should be open-sourced and made publicly available soon, integrated in the MAS-Ter Lab specification (Rossetti et al, 2002(Rossetti et al, , 2005(Rossetti et al, , 2007. As main contributions from the developed work, the general comparison between altitude information retrieval techniques and the developed tool can be considered.…”
Section: Discussionmentioning
confidence: 99%